Coupling of reactor transient simulations via the SALOME platform. (April 2019) - Aydemir, N.U.; Trottier, Alexandre; Xu, T.; Echlin, M.; Chin, T.
Highlights: First results of Canadian Nuclear Laboratories' new PT-HWR transient simulation toolset. SALOME-based coupling of ARIANT (formerly known as CATHENA4) and NESTLE-C. Results for a stylized 20% LBLOCA are presented. Abstract: Canadian Nuclear Laboratories has developed a toolset of coupled reactor transient simulation codes for pressure tube heavy water reactors. This paper presents the first demonstration of the toolset's capabilities, using a hypothetical 20% reactor inlet header break (critical break) scenario. This scenario induces strong feedback between thermalhydraulic and reactor physics phenomena, owing to a positive coolant voiding coefficient. The scenario was simulated using the advanced thermalhydraulics code ARIANT and the reactor physics code NESTLE-C, coupled together using the SALOME platform. This paper summarizes recent advances in ARIANT, the coupling methodology, and the results of the transient simulation.